2019
DOI: 10.1111/bph.14578
|View full text |Cite
|
Sign up to set email alerts
|

Treasure troves of pharmacological tools to study transient receptor potential canonical 1/4/5 channels

Abstract: Canonical or classical transient receptor potential 4 and 5 proteins (TRPC4 and TRPC5) assemble as homomers or heteromerize with TRPC1 protein to form functional nonselective cationic channels with high calcium permeability. These channel complexes, TRPC1/4/5, are widely expressed in nervous and cardiovascular systems, also in other human tissues and cell types. It is debatable that TRPC1 protein is able to form a functional ion channel on its own. A recent explosion of molecular information about TRPC1/4/5 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 107 publications
(287 reference statements)
2
42
0
Order By: Relevance
“…Activation of TRPC channels by lipids is discussed by [55]. Important progress has been recently made in TRPC pharmacology [ 692,529,372,87]. TRPC channels regulate a variety of physiological functions and are implicated in many human diseases [248,56,759,879].…”
Section: Trpc (Canonical) Familymentioning
confidence: 99%
“…Activation of TRPC channels by lipids is discussed by [55]. Important progress has been recently made in TRPC pharmacology [ 692,529,372,87]. TRPC channels regulate a variety of physiological functions and are implicated in many human diseases [248,56,759,879].…”
Section: Trpc (Canonical) Familymentioning
confidence: 99%
“…The novel and most important findings of this study are that we identify TRPC1/4/5 channels as the critical mediator for the development of opioid‐induced analgesic tolerance and hyperalgesia. Previous studies have shown that TRPC1/4/5 channels are implicated in a variety of neurological diseases and disorders including memory, seizure, fear, anxiety, HD as well as pain 9,15,18,22,39‐42 . A recent study reported that TRPC1/4/5 channels are involved in spatial working memory and learning/adaption, combined deletion of TRPC1, TRPC4, and TRPC5 displayed reduced hippocampal synaptic transmission and deficits in working memory 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Seven different TRPC subtypes have been identified to date, i.e., TRPC1-7, which can form either homo-or heteromeric channels. Heteromeric channels formed by TRPC1/5, TRPC1/3, TRPC1/4, TPRC3/4, TPRC4/5 (15), and TRPC1/4/5 (17) have been described. TRPC1, 3, 4, 5, 6, and 7 isoforms are widely expressed in a variety of human tissues and cell types (e.g., endothelial cells, fibroblasts, and muscle cells including cardiomyocytes) (18).…”
Section: Trpc Channel Structure and Distributionmentioning
confidence: 99%
“…Intriguingly, recent studies have reported several selective small-molecule inhibitors for TRPCs. Pico145 and HC7090 selectively inhibit TPRC1/4/5 complex channels, while ML204 selectively blocks the TRPC4 channel (less selective to TRPC5) (17,53). Another small molecule AC1903 has been identified as being more selective for TRPC5 channels (56).…”
Section: Trpc Channel Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation